We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
57
1
avatar+-6 

What is (f⋅g)(x)?

 

f(x)=x3−4x+2

g(x)=x2+2

 

Enter your answer in the box.

(f⋅g)(x)=

 May 16, 2019
 #1
avatar+101420 
+1

f(x)  = x^3 - 4x + 2

g(x)  = x^2 + 2

 

(f * g) (x)  =  ( x^3 - 4x + 2)  ( x^2 + 2)  =

 

x^5 +  2x^3  - 4x^3 - 8x + 2x^2 + 4 =

 

x^5 - 2x^3 + 2x^2 - 8x + 4

 

 

cool cool cool

 May 16, 2019

18 Online Users

avatar
avatar
avatar
avatar